Viltanpassad röjning längs skogsbilvägar som en foderskapande åtgärd för älgen - Forslund, Ida (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2012)
The moose is a keystone species in the boreal forest ecosystem, but the dense Swedish population do cause some serious problems. From a forestry perspective, their browsing on young Scot pine (Pinus sylvestris) causes extensive losses of revenue. Adjusting the cleaning along roadsides of low trafficked forest roads can favour the production of plant species preferred by the moose. This is thought to redirect the moose´s browsing to the roadsides and thereby decrease the damages on commercial forest. The aim of this study has been to present a first evaluation of the vegetation in roadsides, one year after wildlife-adapted roadside clearing has been undertaken. In the wildlifeadapted clearing operation, the roadside was widened by removal of some trees in the forest edge whereupon a complementary clearing with a conventional chain flail was conducted. The wildlife-adapted roads were compared to control roads where clearing with a chain flail, but no cutting of larger trees had taken place. The amount of vegetation, species composition and utilization rates one year after clearance was compared between the two treatments. The results showed that plant species composition was similar for wildlife-adapted and conventional cleared roadsides. The width of the cleared zone was wider in wildlifeadapted roadsides, but even so no more moose forage could be found there compared with the control roadsides. One possible explanation could be an initial difference in width of the roadside before the clearing took place. Another explanation might be that differences in for example site index, soil structure and hydrology was more important for forage production than the clearing treatment. This highlights the importance to select suitable roads for wildlife-adapted clearing. No difference in browsing frequency was found between the treatments, but there was a difference between the cleared zone closest to the road and the extra zone where trees had been removed in the wildlife-adapted roadsides. The frequency of browsing, as ...